REGISTER ANALYSIS OF KIT KAT’S ADVERTISING POSTER - Fajar Khoiriah, Umul; Laila, Malikatul; Haryati, Dwi (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
This research aims to analyze the advertising poster of Kit Kat as a producer of chocolate product by the register analysis. The research approach is descriptive qualitative. The research utilizes the register analysis comprising the context of culture, context of situation, the activity sequence and text structure, and interpretation of the interpersonal meaning of the text. Each of the analysis has function to give a clear picture of the implementation and evaluation of the poster advertising of Kit Kat in targeting its consumers. Moreover, Kit Kat can understand the social situation in especially in Indonesia and compare this advertising poster to understand consumers deeper and more comprehensive in order to be successful in delivering the message.